Regulation of motor vehicle advertising: toward a framework for compliance research - Donovan, Robert; Fielder, Lynda; Ewing, M.; Ouschan, Robyn (Journal of the Australasian College of road Safety, 2011)
There is concern that certain content within some motor vehicle television advertising may negatively influence the driving attitudes and behaviours of viewers, particularly young people, and hence have a negative impact on road safety. In recognition of this concern, many developed countries have adopted a selfregulatory approach to motor vehicle advertising. The basic elements of self-regulation are a code of practice or guiding principles governing advertising content and the establishment of a process for hearing and adjudicating complaints about alleged breaches of that code. However, as in other areas, the effectiveness of self-regulation is being questioned in that many motor vehicle advertisements in Australia and elsewhere appear non-compliant with self-regulatory codes. Applying lessons from studies of alcohol advertising, this paper first reviews the research assessing the content of motor vehicle advertising. A suggested research framework is then proposed to inform the development of motor vehicle advertising regulatory codes where they do not exist, and to better monitor compliance with codes where they do exist. The research framework suggested includes expert content analysis of ads, the impact of advertising on risk-taking cognitions and decisions in computer-simulated traffic situations, and assessing audience perceptions of, and reactions to, messages in advertisements mapped against regulatory code content. An example of audience reaction research is also presented.